Comparative metabolomic analysis of Tempe from velvet bean, soybean, and their combination - Ramdhani, Rizal Pauzan; Tryas, Anisha Ayuning; Astawan, Made; Wresdiyati, Tutik; Sardjono, Ratnaningsih Eko; Rafidha Irdiani; Putri, Sastia Prama (Hasanuddin University Food Science and Technology Study Program, 2025)
Tempe, an Indonesian fermented soybean product, is a popular choice as a source of protein. Currently, Indonesia is very dependent on imported soybeans. Therefore, using local beans as raw material for tempe is necessary to reduce import dependence. Velvet beans (Mucuna pruriens) are legumes that have not been well utilized because they have many anti-nutritional compounds. Velvet beans have high carbohydrate and protein contents and other metabolites that can be utilized as antioxidant functional foods.Therefore, this research aims to analyzed the metabolites profile and explore the potential of velvet beans to partially replace soybeans in making tempe. Velvet bean seeds (VBS) and the tempe made from soybeans (SBT), velvet beans (VBT), and their combination (CSVT) were analyzed for metabolites profile by Gas Chromatography-Mass Spectrometry (GC-MS), and antioxidant activity by DPPH test (IC50). Multivariate Principal Component Analysis (PCA) of the metabolomics study showed that all samples were separated based onPrincipal Component (PC) 1 with 58.3% variation caused by fermentation process. It was shown that organic acids and sugar derivatives were on the positive axis, while amino acids were on the negative axis. In addition, the samples were separated based on PC2 with a variation of 35.8%, which was caused by differences in its bioactive components. Allantoin and DOPA compounds were on the negative axis, while genistein and daidzein were on the positive axis. The lowest IC50 value for tempe was found in VBT (361 ppm),then followed by CSVT (2,216 ppm) and SBT (15,704 ppm). These results indicate that adding velvet beans to make tempe can increase its antioxidant capacity. CSVT had more diverse metabolites, which could increase their antioxidant activity. Furthermore, CSVT presents a promising avenue for local functional food diversification, particularly in supporting efforts to reduce the consumption of imported soybeans.